AB0091 Mechanical exposure and diacerein treatment modulates integrin-fak-mapks mechanotransduction in human osteoarthritis chondrocytes. (12th June 2018) - Lohberger, B.; Weigl, L.; Mann, A.; Kullich, W.; Leithner, A.; Steinecker-Frohnwieser, B.
Abstract : Background: Progression of osteoarthritis (OA) is characterised by destruction of articular cartilage, thickening of subchondral bone, and formation of osteophytes. The disease modifying OA drug (DMOAD) diacerein functions as a slow acting drug through anti-inflammatory, anti-catabolic, and pro-anabolic effects on cartilage and the synovial membrane. Mechanical loading of joint tissue directly affects the homeostasis of matrix degrading enzyme production and matrix repair. Objectives: To explore the impact of diacerein and moderate mechanical stimulation on the anabolic metabolism of OA and non-OA chondrocytes, as well as on the integrin-FAK-MAPKs signal transduction cascade in these cells. Methods: Mechanical stimulation was applied in terms of three different intensities by the Flexcell tension system. Influence on catabolic parameters such as MMPs, ADAMTS, and IL-6 were assessed by qPCR. Changes in phosphorylation of FAK, STAT3 as well as MAP kinases were verified by western blot analysis. Intracellular calcium was measured fluorimetrically using fura-2. Results: Mechanical stimulation at moderate intensity (SM/SA) proved to be most efficient in terms of reducing production of matrix degrading enzyme and IL-6 expression. Treatment with diacerein by itself and diacerein in combination with SM/SA reduced phosphorylation of FAK and STAT3, which is more pronounced in OA cells. Pretreatment with diacerein for 7 days resulted in an increase in the sensitivity to Yoda1, the agonist for the mechanically activated ion channel Piezo1. However, in OA cells a significant reduction in Piezo1 expression was observed following treatment with diacerein. Conclusions: Cyclic tensil strain can reduce matrix destroying enzymes, and when used in combination with diacerein, the activity of integrin signalling components is changed. The observed effects can be mainly attributed to diacerein's capacity to modulate STAT3 and Piezo1, which are both potential targets to prevent the progression of OA. Disclosure of Interest: None declared